Strategies for implementing a digital process for requests letters rogatory or judicial assistance in Ecuador - Cadena Almeida , Alexandra Geovanna (2025)
Implementing a digital process for letters rogatory and judicial assistance requests in Ecuador requires a strategic approach to enhance efficiency and transparency. First, it's essential to revise the legal framework to validate digital procedures. A secure and centralized online platform should be developed, incorporating encryption and digital signatures. Coordination among institutions like the Judicial Council, Ministry of Foreign Affairs, and Public Prosecutor's Office is vital. Training programs must be implemented to prepare staff and legal professionals. Integration with international systems will ensure interoperability and compliance with global standards. A pilot phase can help test the system in selected jurisdictions before national deployment. Stakeholder engagement and awareness campaigns will foster broader acceptance. ongoing monitoring, user feedback, and continuous updates are necessary for long-term success and sustainability. These strategies will modernize Ecuador’s approach to international judicial cooperation and reduce delays in the exchange of legal documents between jurisdictions.